Regional Products in the Central and Eastern European Countries that Acceded to the European Union in May 2004 - Feltynowski, Marcin (Comparative Economic Research. Central and Eastern Europe, 2013)
This article presents information about regional products registered by those Central European countries which joined the European Union structures in May 2004. Their membership facilitated the registration of regional products and their participation in the EU’s registration procedures. Regional and local products registered in the area of a country can become a base for the promotion of regional tourism in the regions of origin of these products. The brand recognition of these regional products also becomes a basis to improve the quality of the agricultural products and foodstuffs. This article presents the activities of the Central European countries which are members of the EU since 2004 in their registration of regional products. The presented data shows how many products were registered within each group of products, protected by the marks: Protected Designation of Origin, Protected Geographical Indication, and Traditional Speciality Guaranteed. Verification of the statistical data allows for analysis concerning the product class, as defined in the EU directives.